The human alphabet - Kane, John.; Pilobolus Dance Theatre (New Milford, Conn. : Roaring Brook Press, 2005)
An alphabet made of people -- here are the 26 familiar letters of the alphabet and images to illustrate them, each made with ingenious grips, bends and twists of the human form.
A Junior Library Guild selection.
Keywords: English language -- Alphabet -- Juvenile literature; Human body -- Pictorial works -- Juvenile literature; English language -- Alphabet; Human body -- Pictorial works; Stories without words